Patterned Wettability Surface for Competition‐Driving Large‐Grained Perovskite Solar Cells. Issue 25 (21st May 2019) - Wang, Yang; Li, Mingzhu; Li, Huizeng; Lan, Yangjie; Zhou, Xue; Li, Chang; Hu, Xiaotian; Song, Yanlin
Abstract: Novel photovoltaic perovskite solar cells (PSCs) with high‐efficient photovoltaic property are largely in thrall to the uncertain perovskite grain size and inevitable defects. Here, inspired by the competitive growth between tree and grass in the forest system, a competitive perovskite grain growth approach via micro‐contact print (MicroCP) method (CD disk as templates) for printing wettability‐patterned substrate is proposed, aiming to achieve large‐grained perovskite and avoid discontinuous perovskite films caused by the low wettability of substrates. A MicroCP process is employed to construct a patterned wettability surface for the perovskite competitive growth mechanism on the electrode surface. This approach modifies the substrates quickly, ensures the uniform coverage of perovskite due to the function of ‐NH2 and Pb 2+ bonds, and converts the perovskite films composed of small grains and pinholes into high‐quality perovskite films, free from pinholes and made up of large grains, resulting in efficiencies over 20% for the MicroCP PSCs. Abstract : Inspired by the competitive growth in forests, a competitive growth mechanism‐driven perovskite grain growth approach via CD disk printing wettability‐patterned substrates is proposed to achieve large grain size and avoid the discontinuous perovskite films caused by the nonwettability of substrates, resulting in efficiencies over 20% for the micro‐contact print perovskite solar cells.